(untitled) (The Research of Medical Science Review, 2025)
Introduction: Overweight and obesity levels in childhood and adolescence are a global public health concern. Worldwide prevalence rates of overweight/obesity have risen considerably in children and adolescents in both developed and developing countries. There is overwhelming evidence that overweight/ obese children and adolescents face social, psychological and physical problems as a consequence of their weight. Obese/overweight children are more likely to suffer from anxiety and depression, be bullied, face discrimination, and report low self-esteem compared to healthy weight counterparts. Furthermore, overweight and obesity has been linked to poor health outcomes and negatively impacts quality of life. Objective: To determine the frequency of Obesity in Children attending the Outpatient Department of Hospital. Material and METHODS: This Descriptive Cross Sectional study was performed NSC ward pediatric unit-1, Sheikh Zayed children hospital, Larkana from 14th February 2023 to 14th August 2023.The study included children between 2 years and 14 years attending the Outpatient Department with complains as mentioned under operational definition. Data was collected regarding the age, height, weight, BMI, gender, monthly income, educational status of father/mother, residential status, diagnosis and reason for attending the clinic was noted. The outcome variable i.e. Obesity was labelled as positive as per operational definition and will be noted in predesigned Performa by the researcher himself. Post stratification, Chi-square/Fisher exact test was also applied to see the effect of effect modifiers on outcome variables. P-value < 0.05 was taken as statistically significant. RESULTS: A total of 300 children were included, the mean age was 8.5 ± 2.0 years, mean height was 100.3 ± 10.5 inches, mean weight was 15.6 ± 1.1kg and mean BMI was 16.6 ± 1.1 kg/m2. 96 (31.9%) were male and 204 (68.1%) were female. Most of the children had diarrhea 153 (51%), 81 (27%) had asthma, 57 (19%) had pneumonia, 2 (0.6%) had UTI and 7 (2.3%) had headache. Out of 300 children, 57 (19%) were obese. CONCLUSION: Current study concludes that there is a high proportion of the children attending pediatric OPD were obese.